PENINGKATAN MUTU PENDIDIKAN NASIONAL MELALUI PROGRAM SERTIFIKASI (EDUKASI: Jurnal Penelitian Pendidikan Agama dan Keagamaan, 2017)
AbstractAs professionals, teachers are obliged to have an academic qualification and competency that are proved with their professional certification. It is required for those teachers with an S1 and D4 educational level to have professional certification and follow the certification process through the examination of teacher competence, the observation of teacher at classroom, portofolio and peer evaluation. Next, after passing the certification test, teachers are entitled to earn benefits as professional teachers equal to one time basic salary. Therefore, it is expected that teacher performance have to be more optimal to improve the quality of national education.
Keywords: quality of education; academic qualification and competency; professional certification